QUALITATIVE ANALYSIS OF STRATEGIES AFFECTING SUSTAINABLE LIVELIHOODS IN THE NORTHERN VILLAGES OF ANDAR DISTRICT, GAZNI PROVINCE, AFGHANISTAN - Abdul Matin Miani; Habibullah Hamayoun; Mahmood Hemat (International Journal of Food and Agricultural Economics, 2022)
The present study is one of the qualitative researches that the grounded theory method (Strauss and Corbin approach) has been used to analyze the data. In-depth interviews and observations were used to obtain data. In qualitative research, in-depth interviews and observations are common data collection approaches. Despite the fact that in-depth interviews and observations are two separate methodologies, both aim to gain a thorough grasp of the situations under investigation. Purposive sampling and snowball sampling techniques were used to collect data. The ATLAS.TI software was used to perform three steps of data analysis: open coding, axial coding, and selective coding. according to the research results, it can be said that strategies for achieving sustainable livelihoods such as Rural industrialization, use of solar energy, strengthening of rural housing, effectiveness of factors of production, breeding of native poultry in yard, Eugenic dairy cows, attention to rural research, development of nonagricultural occupations can improve the living conditions of villagers.